SUBSTITUSI FILLER PADA CAMPURAN ASPAL DENGAN FLY ASH DAN SERBUK BATU BATA - Mohammad Zainudin Abdillah; Dwi Kartikasari (Litbang Pemas - Universitas Islam Lamongan, 2018)
Asphalt concrete wearing course as a wear layer in highway pavement layer, Is the top layer in flexible pavement. In this research will be discussed on the use of Portland cement filler as a reference to compare filler replacement with fly ash and powdered brick with 100% fly ash, 100% powdered brick and 50% fly ash: 50% powder brick. The first step after the aggregate testing, the asphalt and filler material to be used, followed by the manufacture of the specimen with the specified asphalt content. After obtaining the optimum asphalt content for each different filler variation, a Marshall test was performed to obtain flow stability and density values. In this research we get the optimum asphalt content value of 5,5% for each specimen. The result of this research mixed with good quality using 100% Portland cement filler stability value of 112.19 kg and the lowest using filler 100% fly ash but the result still meet the specifications of clan. While the MQ value with 100% filler of brick powder under specification of Bina Marga is 213. So it can be concluded that a good filler for asphalt concrete wearing course mixture is with Portland cement.